High arsenic (As) content in the Upper Miocene coal matter from TER-1/03 borehole (Terbegovci - Sveti Jurij ob Ščavnici, NE Slovenia) - Markič, Miloš; Brenčič, Mihael (Geologija, 2014)
A composite sample of coal cuttings (depth: 141.0-155.5 m) from the TER-1/03 water supply well in northeastern (NE) Slovenia (Slovenske gorice; locality Terbegovci - Sveti Jurij ob Ščavnici) was analysed for its coal quality (proximate analysis - percent moisture, volatile matter, fixed carbon, ash), calorific value, and major (C, H, O, N, S)-, minor (Si, AI, Fe, Mg, Ca, Na, K, Ti, P, Mn - as oxides)- and trace-elemental (43 elements) chemical composition. The coal was classified as a "normal" humic, high-grade metalignite, similar to coals in the Mura Formation of the Mura-Zala Basin. Unusually high arsenic (As) content of more than 100 µg/g was determined in the investigated coal matter, whereas the Clarke value for the world coals is between 5 and 10 µg/g, as cited by different authors. Besides As, also Sb, V, Mo, U, and W have been found to be enriched in the studied coal.